Hasidism, Haskalah, Zionism: Chapters in Literary Politics - Ḥever, Ḥanan (Jewish Culture and Contexts Series, 2023)
"Hasidism, Haskalah, Zionism reveals how political and literary dialogues and conflicts between the Hebrew literature of the Hasidism, the Jewish Enlightenment, and Zionism interacted with each other in the nineteenth century. Author Hannan Hever uses post-colonial theories and theories of nationality to analyze how Jews used literature to tackle the "The Jewish Question," and set forth their own ideas and preferences regarding their status, control, and treatment as European Jews. In doing so, Hever theorizes the Enlightenment's intellectual aims and cultural influences, tracking how the models of integration crucial to Haskalah gave way to Jewish nationalism in the twentieth century. The readings in this book are theoretically informed, setting forward claims based on detailed textual analyses of Hasidic tales, Haskalah satires, and Zionist narratives. Thus, this book tackles a major interpretative problem visible at the core of modern Hebrew literature - its radical difficulty in distinguishing between the theological components of modern Jewish discourse and its national identity"--